Examining temporal alterations in Social Anxiety Disorder and Posttraumatic Stress Disorder: The relation between autobiographical memory, future goals, and current self-views. (December 2017) - Krans, Julie; Peeters, Manon; Näring, Gérard; Brown, Adam D.; de Bree, June; van Minnen, Agnes
Highlights: Temporal alterations were found in both PTSD and SAD. The strength of these alterations was comparable across PTSD and SAD. Memory recall in PTSD was associated with trauma-related future goals. Memory recall in SAD was associated with current anxious self-views. Self-processing across past, present, and future is relevant for SAD and PTSD. Abstract: The self is a multi-faceted and temporally dynamic construct reflecting representations and beliefs about identity in the past, present, and future. Clinical studies have shown that individuals with Posttraumatic Stress Disorder (PTSD) and Social Anxiety Disorder (SAD) exhibit alterations in self-related processing but these studies have focused primarily on memory. Few studies in PTSD and SAD have examined self-related processing for the present and future, and no studies have directly compared these processes across these two disorders. Individuals diagnosed with PTSD ( n  = 21), SAD ( n  = 21), and healthy controls ( n  = 21) completed cognitive tasks related to the past, present, and future. Disorder congruent temporal alterations were found across both disorders. Further, regression analyses revealed that trauma-related memories were significantly predicted by future goals related to the trauma, whereas social anxiety-related recall was predicted by current socially anxious self-views. Thus, although self-related processing may be common in PTSD and SAD, those aspects of the self most strongly associated with disorder-congruent recall differ by disorder. Self-alterations may be modifiable and developing a better understanding of past, present, and future self-processing might aid in the development of interventions that target these process.